ANALISIS PENGARUH PENANAMAN MODAL ASING, INFLASI DAN INDEKS HARGA KONSUMEN TERHADAP PERTUMBUHAN EKONOMI DI DUA BELAS WILAYAH PROVINSI JAWA TENGAH PERIODE TAHUN 2015-2019 - Nasarudin, Nasarudin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The object of this research is Economic Growth in Central Java. This study aims to analyze the effect of foreign investment, inflation, and the consumer price index on economic growth in Central Java. The data used is time series data from 2015-2019 published by Bank Indonesia, the Central Bureau of Statistics, and the World Bank. The analytical method used in this study is a multiple regression analysis tool with the Ordinary Least Square (OLS) method approach. Based on this study it was concluded that inflation has a significant effect on economic growth in Central Java, while the exchange rate and investment have no significant effect on inflation in Central Java.